Methods of Organizing the Technological Process of Software Development - Mahmudova, Shafagat (Review of Information Engineering and Applications, 2018)
The article provides information on the methods of organizing the technological process of software development. The key point is that if information is processed, it must be used for these three elements It explores the interaction of people, technology and process. Types of technological processes and software development models are analyzed. Technological process is the adjusted sequence of interconnected actions, starting from the moment of initial data generation to the preferred result. Technological processes consist of "technological operations", which, in turn, are shaped by "technological transitions." “Technological transitions” are called a finished part of technological operation implemented with the same tools of technological supply. In other words, technological process is a part of production process, which includes purposeful actions for the determination of the state of subject of labor. The subject of labor includes software development. Software development process in its production is a process of grouping the implementations into separate stages to prepare and design software, and to improve product and project management. It is also known as a life cycle of software. The methodology may include predefined certain results and artifacts generating and finishing the project for software development together with team. The implementations during the phases of technological and innovation process are explained. The methods for effective organization of technological process of software development are shown. Disadvantages of technological process are examined. Possible risks for software projects and their solution ways are revealed.